The Spectacle of the Other: The Politics of Apologetic Representation of Islam in Social Media - Iman Mukhroman; Agus Ahmad Safei; Asep A. Sahid (UIN Sunan Gunung Djati Bandung, 2026)
In today’s digital era, Islamic apologetics has moved away from traditional theological debates and toward more dynamic and widely publicized presentations. Social media now acts as a stage for figures like Bang Zuma to defend their beliefs with bold moves and identity-driven narratives. This mirrors Stuart Hall’s concept of the politics of representation, where other groups are cast as symbolic rivals in cultural struggles over meaning and power. Using Teun A. van Dijk’s Critical Discourse Analysis, this study looks at two of Bang Zuma’s YouTube videos through three angles: macrostructure (big-picture ideological themes), superstructure (how arguments are built), and microstructure (language and style). The results show a symbolic battle that asserts Islam’s dominance while discrediting others. Through deliberate word choice, repeated religious symbols, and a showy communication style, faith becomes a moral performance mixing theology with spectacle. In the end, digital Islamic apologetics works both to defend belief and to put on an ideological show that upholds religious authority while deepening social and religious divides, showing how religion adapts to media logic where representation turns into a contest for meaning and identity.